Pengaruh Olah Raga Permainan Tradisional Hadang Terhadap Kelincahan Siswa - DinDin Bernhardin (STKIP Paasundan Press, 2021)
This study aims to determine the effect of traditional sports hadang on the agility of class XI MIPA 2 SMA Pasundan 1 Bandung. This research is an experimental study with a one-group pretest-posttest design. The population used all class XI students at SMA Pasundan 1 Bandung. Sampling using cluster random sampling technique, with this technique, the number of samples obtained 24 students from class XI MIPA 2. Data obtained from the results of agility tests using the Illinois test in class XI MIPA 2 at SMA Pasundan 1 Bandung shows the average pretest results. 19,283 and the posttest results 17,916. For 4.258 and